Enabling youth in decision making through competent youth work - Lee, Kwan Meng (Human Resource Management Academic Research Society, 2017)
The first primary goals of the Malaysian Youth Policy 2015 is that the youth should be more responsible citizens in initiatives at national, regional, and international levels. This suggests that the youth should therefore be involved in decision making at all levels. And this is where one of the positive assets of Malaysian youth that have been identified is social competency in decision-making. Since those involved in youth work play a role is facilitating the development of the youth, they then have an important role in facilitating the development of this capacity for decision making of the youth. Those in youth work are professionals who work with young people in a range of settings (Commonwealth Secretariat 2012). They can be found in youth clubs, street-based settings, social/welfare services, sports/leisure centres, schools, museums, arts facilities, government agencies, children’s homes, hospitals, among others. Their job roles are diverse from being counselors addressing youth problems to youth development building youth assets in positive youth development, researchers, youth education, and policy makers. All these diverse roles require those in youth work to be equipped with various skill sets guided by theory, best practice, youth principles and values and communication skills. Ultimately those in youth work are in the business of developing youth through which the youth are guided and facilitated to express themselves and become future leaders with decision-making capacities through empowerment. A study was recently conducted to identify the status of youth work practice and the core competencies of Malaysian youth workers for their professionalization. Professionalisation of youth workers is now one of the priorities of the new Malaysian Youth Policy 2015. The study found that Malaysian youth workers have yet to be considered as ‘professionals’ and hence lack the relevant competencies to be professionals. Among the recommendations are competency training for these youth workers, establish professional standards, ethics and practice, and the formation of a youth worker association that will certify and register these professionals in youth work.